(What produces the) best effects on Teacher's ICT use in classroom: Formal training, informal training or neither? - Piedade, João (2012)
This paper presents a study developed with 103 secondary school teachers, which assumed the purpose of analysing the efficiency of two different approaches in teachers’ ICT training, specifically formal and informal courses. This analysis was conducted considering teachers’ perceived impact of formal and informal teachers’ training courses as well as the number of courses attended into two different psychological constructs: (a) teachers’ perception of ICT use in professional activities and (b) computer self-efficacy. Significant differences were possible to identify in these two different formats of training initiatives.